Antioxidant activity of petunias with the heterologous ribonuclease ZRNase II gene infected with tobacco mosaic virus - Potrohov, Andrii; Ovcharenko, Olga; Sosnovskaya, Daria (Innovative Biosystems and Bioengineering, 2022)
Background. Constant changes in environmental conditions cause the development of stress reactions in plants. Under conditions of moderate intensity and temporary action of the stress factor, the strengthening of protective systems and the mobilization of energy resources take place. However, if the stress factor has a long-term effect, the cells begin the processes of lipid peroxidation (LPO), inhibition of energy production and reduction of protein synthesis with its subsequent destruction. Under conditions of excessive stress, there is a balance between antioxidant activity (AOA) and LPO, which is necessary to maintain normal cell function. Oxidation intermediates can serve as inducers and mediators of stress. Phytovirus infection can lead to pathological changes in the body of a plant. The progression of the infectious process in the body of the affected plant is associated with stress reactions and disruption of its normal viability. Objective. We are aimed to assess the degree of progress of stress reactions caused by biotic stressors in control and transgenic (with ZRNase II gene) petunia plants. Methods. Tobacco mosaic virus (TMV) was used to infect petunia plants. The degree of progress of stress reactions in transgenic petunia plants with the ZRNase II gene before and after infection with TMV was studied by POL and AOA indicators. Two genetically distinct lines of petunia (M1 and P5) were used to obtained transgenic plants. To assess the progress of LPO, the accumulation of initial and final products (diene conjugates and malonic dialdehyde) was determined. Results. After the plants transformation, changes in the content of LPO products in leaf tissues were observed. Transgenic plants had a 10–15% higher content of LPO products, which may indicate that the transformation, in some cases, can lead to the progress of stress reactions in plants. Infection with TMV has contributed to the intensification of processes related to the protection of plants from the effects of negative factors. Studies of total AOA have shown that transgenic plants after infection had significantly higher levels (18–30%) of AOA compared with controls, which may be evidence of their increased viability under stress. Conclusions. The positional effect of T-DNA incorporation in genetic transformation may be a stressor for the plant. Transgenic lines differ in terms of LPO and AOA from non-transgenic lines and from each other. After infection with TMV, a 4-fold decrease in AOA was observed in the plants. Effective expression of the ZRNase II gene helps to reduce viral load in certain lines. Lines M1.2 and P5.3 are of greatest interest for further virological studies, as their AOA activity was 18–30% higher than in control plants, which may indicate resistance to viral infection.